Actinobacteria From Desert: Diversity and Biotechnological Applications - Xie, Feiyang; Pathom-aree, Wasu (Frontiers in Microbiology, 2021)
Deserts, as an unexplored extreme ecosystem, are known to harbor diverse actinobacteria with biotechnological potential. Both multidrug-resistant (MDR) pathogens and environmental issues have sharply raised the emerging demand for functional actinobacteria. From 2000 to 2021, 129 new species have been continuously reported from 35 deserts worldwide. The two largest numbers are of the members of the genera Streptomyces and Geodermatophilus, followed by other functional extremophilic strains such as alkaliphiles, halotolerant species, thermophiles, and psychrotolerant species. Improved isolation strategies for the recovery of culturable and unculturable desert actinobacteria are crucial for the exploration of their diversity and offer a better understanding of their survival mechanisms under extreme environmental stresses. The main bioprospecting processes involve isolation of target actinobacteria on selective media and incubation and selection of representatives from isolation plates for further investigations. Bioactive compounds obtained from desert actinobacteria are being continuously explored for their biotechnological potential, especially in medicine. To date, there are more than 50 novel compounds discovered from these gifted actinobacteria with potential antimicrobial activities, including anti-MDR pathogens and anti-inflammatory, antivirus, antifungal, antiallergic, antibacterial, antitumor, and cytotoxic activities. A range of plant growth-promoting abilities of the desert actinobacteria inspired great interest in their agricultural potential. In addition, several degradative, oxidative, and other functional enzymes from desert strains can be applied in the industry and the environment. This review aims to provide a comprehensive overview of desert environments as a remarkable source of diverse actinobacteria while such rich diversity offers an underexplored resource for biotechnological exploitations.